Empowerment: A concept analysis - Dara Febriana (Syiah Kuala University, 2011)
This paper conceptually analyzed the concept of empowerment using the strategies of Walker Avant (2005) the objective is to clarify the meaning of the concept and to clearly identify empowerment characteristic that will provide consistent definition for practice and future research. Empowerment is defined and examined using relevant resources of literatures and selected empirical referents that described empowerment as a complex and multidimensional concept. Within nursing context empowerment can be conceptualized as a combinations of attributes that relate to the empowerer (the client), and attributes that belong to the empowered (that can be both client and nurse). In a broad sense, empowerment is the process that involves two parties or more that are dynamic and multidimensional, where the activity is sharing power, and create mutual relationship, making it possible for people to increase their sense of control and can help optimize their independence. To clearly distinguish between empowerment and other concepts, related concepts are presented and by using related case we compared the concept with empowerment. The analysis demonstrates that the defining attributes of the concept are (1) a helping process, (2) A partnership which values self and others, (3) mutual decision making, identified resources and set goals, (4) opportunity and authority, (5) open communication, (6) freedom to make a choice and accept responsibility and (7) should come with honesty, openness and genuineness. Antecedents of the concept are (1) respect, (2) trust, (3) education or previous knowledge or experience, (4) interpersonal and communication skills, (5) acceptance of people as they are, and (6) shared visions. Consequences of empowerment are (1) enhanced and improved self esteem, (2) ability to set goals and reach goals, (3) a sense of control over life and change process, (4) a sense of hope for the future, (5) increase problem solving ability, (6) better communication and leadership skills, and (7) have the autonomy and responsibility. To understand the concept better all the defining attributes are identified and applied in the model case, while borderline, related and contrary case are also used to explicate the concept. Empirical referents were also provided. There are limited tools available to measure empowerment, which create the availability to develop tools to measure empowerment based on the context. In conclusion, empowerment is useful and significant concept for nursing practice, administration, education and research. Empowerment emphasizes in engaging the resources within self to create well - being. Therefore, clients need to become aware of their resources and need to purposefully participate in working toward the attainment of heath goals